DILI and Drug Development: A Regulatory Perspective - Avigan, Mark I. (Seminars in Liver Disease, 2014)
The assessment of risk for serious, life-threatening drug-induced liver injury (DILI) associated with a suspect drug, biological agent, or herbal product depends on an iterative analysis of pre- and postmarket datastreams. Because serious cases of idiosyncratic DILI are typically rare, regulatory scientists seek strategies that accurately predict from clinical trial data which study drugs will be likely to cause these events in a large postmarket treatment population, e.g., through the identification of cases that are consistent with Hy's law. This objective is only achievable if rigorous standards in study subject monitoring, data collection and analysis of liver injury cases for causality are followed. In the future, the development of more effective predictive and analytic tools in preclinical and clinical testing will provide a framework to reliably identify new agents that have hepatotoxic profiles as well as those individuals who are susceptible to develop serious DILI.
Keywords: drug-induced liver injury; hepatotoxicity; biomarkers; clinical trials; postmarketing drug-risk evaluation